The controversial humanities (Journal of Parents and Teachers, 2014)
Education is responsible for training and "building" people with a certain ethical model and specific values. Therefore, the idea of ​​seeking only knowledge is outdated and distorted in relation to today's society, because it seeks to act personally, in relation to the citizen and in the workplace. Under this premise, teaching must be learned and taught humanistically, that is, not only the concepts or contents as if they were "dead or off", but everything that they have entailed, their activity and their contribution to the training of people with the aim of solving not only theoretical problems, but practical problems that appear to a greater extent.
Keywords: Education; Humanities; model; persons; politics; politicians; educators; Ethics; personal life; citizen life; laboral life; society